(untitled) (Revista Argentina de Musicología, 2016)
The celebration of the centenary of Alberto Ginastera (1916-1983) offers an opportunity to examine the current state of scholarship on the composer. This study begins with a brief review of the Ginastera literature in order to evaluate the achievements and challenges of previous research and envision new paths for the next Ginastera century. One of the challenges scholars face is that the Ginastera repertoire is divided into two parts: 1) the repertoire with opus numbers authorized by the composer and 2) the unnumbered repertoire that he produced outside the space of his official works. This article claims that one should address both facets of the composer’s repertoire because together they represent two interconnected parts of his creative production. To support this claim, this article presents a case study of the composer’s first film score for the motion picture, Malambo (1942). It suggests that this composition exemplifies the same inclination toward modernity that characterizes other Ginastera works of the period. Ultimately, this analysis leads us to examine the role of musicologists in relation to their objects of study and reflect on the aesthetic and ethical issues that arise from the decision to reconstruct a repertoire that the composer himself suppressed.